The effect of exchange rate and palm oil price towards export earnings of palm oil industry in Malaysia / Noordina Hassan - Hassan, Noordina (2007)
Palm oil industry has contributed the biggest income to the countries for many years. Moreover, palm oils have emerged as one of the most important oils in the world's oils and the market of fats. Its unique composition makes it versatile in application for food manufacturing as well in the chemical, cosmetic and pharmaceutical industries. For this study, it is focus on the earnings from the export of palm oil industry in Malaysia. There are still lack of study investigate within these area. Since Malaysia is the world largest producer of palm oil, the questioned raised on the factor that influence the export value (RM) of palm oil industry in Malaysia. The objective of the study is to identify the factor that affecting the total export value of Malaysian palm oil. The independent variables are Malaysian exchange rates of RM/US$, crude palm kernel oil (CPKO) price and crude palm oil (CPO) price. While, the dependent variable is export value of Malaysia palm oil (RM). This study consists of 6 year monthly observation for the period between 1995 until 2000. The data about this study is taken from secondary data which is from internet and database. Statistical tools has used in the study is Multiple Linear Regression in order to find the findings of the research. From the study, it found that the export value of Malaysia palm oil is influences by exchange rate, crude palm kernel oil (CPKO) price, and crude palm oil (CPO) price.